Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3109/10826084.2015.1092991
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Incidence of HIV and HCV Among New Injecting Drug Users With a Large Proportion of Migrants—Is Prevention Failing?

Abstract: A large proportion of PWID in Catalonia are new injectors, a subgroup with a high level of both sexual and parenteral exposure and a high incidence rate of HIV/ HCV infections. It is important to improve early diagnosis of these infections among this group, in particular among migrants. To identify and address risk factors for homelessness PWID should be a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 32 publications
2
37
0
6
Order By: Relevance
“…Sociostructural factors such as unemployment, poverty, discrimination, and marginalization are all risk factors for problematic substance use that disproportionately affect international migrant populations (Durrant & Thakker, 2003; Hacker et al, 2011). Studies in North America, Europe, and Australia have observed that migrants who inject drugs have higher rates of undiagnosed blood-borne infections and lower levels of access to healthcare and preventative services compared with other PWID (Brouwer et al, 2009; Folch et al, 2016; Maher et al, 2004; Swift et al, 1997). Therefore, addressing disparities experienced by migrants may be critical in mitigating risk environments for injection initiation and blood-borne disease.…”
Section: Migration Classes and Injection Initiationmentioning
confidence: 99%
See 3 more Smart Citations
“…Sociostructural factors such as unemployment, poverty, discrimination, and marginalization are all risk factors for problematic substance use that disproportionately affect international migrant populations (Durrant & Thakker, 2003; Hacker et al, 2011). Studies in North America, Europe, and Australia have observed that migrants who inject drugs have higher rates of undiagnosed blood-borne infections and lower levels of access to healthcare and preventative services compared with other PWID (Brouwer et al, 2009; Folch et al, 2016; Maher et al, 2004; Swift et al, 1997). Therefore, addressing disparities experienced by migrants may be critical in mitigating risk environments for injection initiation and blood-borne disease.…”
Section: Migration Classes and Injection Initiationmentioning
confidence: 99%
“…Migrant populations have also been shown to be at risk of initiating injection drug use (IDU) (Folch et al, 2016; Horyniak, Melo, Farrell, Ojeda,& Strathdee, 2016a; Ojeda et al, 2011), especially those populations whose migration pathways traverse drug trafficking regions (Beyrer et al, 2000; Rachlis et al, 2007). Relatedly, dual epidemics of IDU and blood-borne disease have been observed across international borders and drug trafficking routes globally (Beyrer et al, 2000; Rachlis et al, 2007; Strathdee, Magis-Rodriguez, Mays, Jimenez, & Patterson, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In high income countries, most new HCV infections occur among people who inject drugs (PWID), with an estimated incidence of 2–46 infections per 100 person-years (Backmund, Reimer, Meyer, Gerlach, & Zachoval, 2005; Folch et al, 2016; Grebely & Dore, 2011; Hajarizadeh, Grebely, & Dore, 2013; Maher, Li, Jalaludin, Chant, & Kaldor, 2007; Page, Morris, Hahn, Maher, & Prins, 2013; van den Berg et al, 2007). While PWID are disproportionately burdened by HCV (prevalence ranging from 60% to 80%), almost half are unaware of their status (Nelson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%